Video Games as a Complementary Therapy for Schizophrenia: A Systematic Review. Issue 2 (March 2022) - Molina, Rosa; Díaz-Oliván, Isaac; Girela, Braulio; Moreno, Manon; Jiménez-Muñoz, Laura; Delgado-Gómez, David; Peñuelas-Calvo, Inmaculada; Baca-García, Enrique; Porras-Segovia, Alejandro
Abstract : Background: Schizophrenia is a prevalent and serious disorder. Video games have shown potential as an aid in health care for people who suffer from schizophrenia. Although video games may contribute benefit in the treatment of schizophrenia, reviews on this topic are scarce. In this article, we systematically review the evidence concerning video game-based therapeutic interventions for people diagnosed with schizophrenia. Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The review protocol was registered in the PROSPERO database. We searched 4 databases—PubMed, Web of Science, EMBASE, and clinicaltrials.gov—to identify original studies exploring video game-based therapeutic interventions for people with schizophrenia. Results: After initial screening, full-text review, and study selection, 11 articles were included in the review. Most studies used video consoles as the platform, with a minority using a personal computer. Video game-based therapeutic interventions were well accepted and generally effective in improving cognitive areas. Conclusions: Cognitive training could be one of the main mechanisms underlying the usefulness and effectiveness of video game-based therapeutic interventions. Software optimization and greater collaboration between developers and health care professionals are some of the priorities for future research in this area.